Strategi Pengembangan Lahan Budidaya Jagung dan Padi di Wilayah Daratan Kabupaten Sumenep, Madura, Jawa Timur: Land Development Strategies for Corn and Paddy Cultivation in the Mainland of Sumenep Regency, Madura, East Java - Khairul Anam; Khursatul Munibah; Untung Sudadi (Jurnal Ilmu Tanah dan Lingkungan, 2020)
The main challenges in improving food security in Indonesia have been solving problems related to decreasing ratio of available land area suitable for staple-food crops cultivation againts their demands. Existing farmland in the mainland of Sumenep Regency, Madura, which is one of the food estates of East Java Province, is cultivated mainly for corn and paddy that respectively occupies 55% and 20,67% of the areas. This research aims to (a) analyze available lands suitable for corn and paddy cultivation development, (b) determine food balance of both crops and their cultivation areas needed for fulfilling their demands; and c) formulate priority of land development strategy for both crops to support food security in the mainland of Sumenep Regency. This study was conducted by applying maps visual interpretation, overlay and matching techniques aided with Geographic Information System softwares, and descriptive methods as well. The available lands suitable for corn and paddy cultivation in the research area covered areas of ​​respectively 20.078 and 10.565 Ha. The food balance for maize and rice showed a surplus of respectively 254.334 and 1.483 tons at year 2033, and the cultivation area needed to fulfill the projected demand of both commodities were respectively 10.774 and 17.673 Ha. This indicated an increasing number of local people that changed their custom in staple food consumption to a mixed maize-rice with higher rice portion. Three priorities of land development strategy were elaborated and discussed.